2012
DOI: 10.1007/s13524-012-0129-5
|View full text |Cite
|
Sign up to set email alerts
|

Diverging Destinies: Maternal Education and the Developmental Gradient in Time With Children

Abstract: Using data from the 2003–2007 American Time Use Surveys (ATUS), we compare mothers’ (N = 6,640) time spent in four parenting activities across maternal education and child age subgroups. We test the hypothesis that highly educated mothers not only spend more time in active child care than less educated mothers, but that they alter the composition of that time to suit children’s developmental needs more than less educated mothers. Results support this hypothesis: highly educated mothers not only invest more tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
388
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(443 citation statements)
references
References 42 publications
(41 reference statements)
22
388
0
3
Order By: Relevance
“…Moreover, higher SES parents allocate more time and effort in providing their children a nurturing environment (Kalil et al, 2012). Thus, the effects of SES on externalizing may be partially accounted for by differences in parenting.…”
Section: Socioeconomic Advantage As a Protective Factormentioning
confidence: 99%
“…Moreover, higher SES parents allocate more time and effort in providing their children a nurturing environment (Kalil et al, 2012). Thus, the effects of SES on externalizing may be partially accounted for by differences in parenting.…”
Section: Socioeconomic Advantage As a Protective Factormentioning
confidence: 99%
“…An analysis of Denmark shows that greater educational assortative mating has increased inequality, but due to shifting educational distributions by gender (i.e., education increasing for both men and women -but more so for women) rather than partner choice (Breen and Andersen 2012). Certainly, families with greater socioeconomic resources are able to make greater investments (of both time and money) in their children (Kalil 2015;Kalil, Ryan, and Corey 2012;Lareau 2003), and these differential investments may be an important factor in growing inequality, especially across generations (Lundberg, Pollak, and Stearns 2016;Reeves 2017). And as Cooke (see Chapter 11) describes, countries differ greatly in the share of national resources that are invested in families; when countries provide greater baseline support, there is likely less variation by parents' income in how much they invest in children.…”
Section: Answered and Unanswered Questions About Family Inequalitymentioning
confidence: 99%
“…Sociological studies of time diary data found that highly educated mothers adapt particularly well to the growing needs of their children over the course of their development (Kalil et al 2012), although more studies point to the increasing engagement of highly educated fathers in child-related activities -particularly among very young infants (Gershuny 2000;Gracia 2014). Even if women used to be major actors in securing childcare (Pungello and Kurtz-Kostes 1999), changes in the relative position of women might have rendered decisions on childcare more of a shared decision by a couple, thereby allowing fathers to spend more time with their children (Bianchi et al 2004).…”
Section: Parental Care and Social Inequalitiesmentioning
confidence: 99%